2015
DOI: 10.1159/000381355
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Occlusal Caries Lesion Management in France from 2002 to 2012: A Persistent Gap between Evidence and Clinical Practice

Abstract: A survey conducted in 2002 among French general dental practitioners (GPs) showed variations between treatment decisions and a tendency towards early restorative intervention for caries. The aims of the present questionnaire survey were to investigate, among a random sample of 2,000 French GPs, the management decisions for occlusal lesions in 2012 and to compare the results to those obtained in 2002. The response rate was 41.9%. The majority of the respondents (60.7%) would postpone their restorative decisions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
22
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 45 publications
6
22
1
1
Order By: Relevance
“…This is in contrast with the assessment of American dental professionals [Gordan et al, 2010], in which restorative treatment of occlusal lesion located in the inner enamel and outer dentin in low caries risk individuals was recommended by more than 50 and 90% of dentists, respectively. A similar trend was reported for French dentists, where 40% indicated restorative treatment of occlusal enamel lesions [Doméjean et al, 2015]. Likewise, a systematic review on treatment decisions for occlusal lesions, including studies from 17 countries, reported that 12% of dental professionals indicated restorative treatment for occlusal lesions with enamel discoloration or cavitation without clinical or radiographic dentin involvement.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…This is in contrast with the assessment of American dental professionals [Gordan et al, 2010], in which restorative treatment of occlusal lesion located in the inner enamel and outer dentin in low caries risk individuals was recommended by more than 50 and 90% of dentists, respectively. A similar trend was reported for French dentists, where 40% indicated restorative treatment of occlusal enamel lesions [Doméjean et al, 2015]. Likewise, a systematic review on treatment decisions for occlusal lesions, including studies from 17 countries, reported that 12% of dental professionals indicated restorative treatment for occlusal lesions with enamel discoloration or cavitation without clinical or radiographic dentin involvement.…”
Section: Discussionsupporting
confidence: 65%
“…Previous studies on treatment decisions for the management of occlusal caries have shown substantial variations among dental general practitioners [Mejàre et al, 1999;Espelid et al, 2001;Bader and Shugars, 2006], particularly as to whether operative treatment is required [Gordan et al, 2010;Rindal et al, 2014;Doméjean et al, 2015]. Dentists' treatment decisions have mainly been based on caries risk assessment, clinical characteristics of the occlusal lesions [Mejàre et al, 1999;Espelid et al, 2001;Nascimento et al, 2010], and radiographic signs of caries demineralization [Makhija et al, 2014].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The second limitation which is discussed is the nature of non-validated self-reports which may not reflect the actual behaviour. The strength of this study is the relatively high response rate and the fact that the three national cross-sectional studies of 1983-2009 have reflected changes which are consistent with international trends Espelid et al, 2001;Vidnes-Kopperud et al, 2011;Doméjean et al, 2015].…”
Section: Discussionmentioning
confidence: 98%
“…7,8,42-54 For example, a French survey undertaken in 2002 showed that almost 50% of respondents would restored an occlusal lesion confined to enamel in patients with low caries risk. 45 Espelid et al showed in 1995 and 1996 that 30% of Scandinavian dentists would undertake chose restorative treatment options for lesions radiographically confined to enamel. 53 Whilst support for micro-invasive treatment, i.e.…”
Section: Commented [Sf3]mentioning
confidence: 99%